2017
DOI: 10.1080/15592294.2017.1403691
|View full text |Cite
|
Sign up to set email alerts
|

The fetal programming effect of prenatal smoking onIgf1randIgf1methylation is organ- and sex-specific

Abstract: The impact of prenatal smoke exposure (PSE) on DNA methylation has been demonstrated in blood samples from children of smoking mothers, but evidence for sex-dependent smoke-induced effects is limited. As the identified differentially methylated genes can be associated with developmental processes, and insulin-like growth factors (IGFs) play a critical role in prenatal tissue growth, we hypothesized that PSE induces fetal programming of Igf1r and Igf1. Using a mouse model of smoking during pregnancy, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
2
19
0
1
Order By: Relevance
“…This beneficial effect of NAC was not found in livers of male offspring, suggesting a tissue specific effect of NAC. A tissue-specific response, with a distinct DNA methylation pattern, was observed in several models of prenatal exposure to stressors [17][18][19]. Uncovering the DNA methylome in muscle, liver and pancreatic islets might shed light on the tissue-specific outcomes of prenatal NAC administration.…”
Section: Discussionmentioning
confidence: 99%
“…This beneficial effect of NAC was not found in livers of male offspring, suggesting a tissue specific effect of NAC. A tissue-specific response, with a distinct DNA methylation pattern, was observed in several models of prenatal exposure to stressors [17][18][19]. Uncovering the DNA methylome in muscle, liver and pancreatic islets might shed light on the tissue-specific outcomes of prenatal NAC administration.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking has adverse effects on health and is associated with changes in epigenetic marks. Prenatal smoke exposure affects DNA methylation in blood cells from children of smoking mothers [ 185 , 186 ]. Smoking may induce DNA methylation alterations in cells of both the innate and adaptive immune systems [ 187 ].…”
Section: Epigenetics and Agingmentioning
confidence: 99%
“…This was related to sex-dependent differences in promoter methylation of Igf1r . This was recently confirmed in a second study using a prenatal smoke model in C57Bl/6 mice, which also showed that Igfr1 CpG methylation was organ- and sex-specific 64 . The difference to our study could be due to the different time point of analysis as the observed increase in Igf1 levels in our study was only found at E18.5, but not at PND 21 and we did not investigate d30.…”
Section: Discussionmentioning
confidence: 55%